The Palgrave Handbook of Textbook Studies (Palgrave Macmillan US, 2018)
This volume examines the present status and future trends of textbook studies. Cutting-edge essays by leading experts and emerging scholars explore the field's theories, methodologies, and topics with the goal of generating debate and providing new perspectives. The Georg Eckert Institute's unique transdisciplinary focus on international textbook research has shaped this handbook, which explores the history of the discipline, the production processes and contexts that influence textbooks, the concepts they incorporate, how this medium itself is received and future trends. The book maps and discusses approaches based in cultural studies as well as in the social and educational sciences in addition to contemporary methodologies used in the field. The book aims to become the central interdisciplinary reference for textbook researchers, students, and educational practitioners. .